Integrating the Institution of Mediation into Judicial Practice: A Comparative Analysis of Foreign Paradigms and the National Model - Adilova, Marjangul (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The chronic congestion of civil court dockets globally necessitates a structural pivot from strictly adversarial litigation toward integrated Alternative Dispute Resolution (ADR) mechanisms. This empirical legal investigation evaluates the functional efficacy of court-annexed mediation, contrasting established foreign frameworks with the developing national model. The research quantitatively assesses the impact of integrating formal mediation protocols into standard civil procedure, analyzing a stratified sample of 500 commercial and family disputes adjudicated between 2020 and 2024. By benchmarking the national voluntary mediation framework against the mandatory "opt-out" paradigms utilized in Italy and the judge-mediator (Güterichter) system in Germany, the study maps the procedural friction points inhibiting local ADR adoption. The data reveals that while voluntary referrals yield a modest 18.5% uptake, implementing a mandatory initial mediation session increases successful out-of-court settlements to 62.4%. Consequently, the average lifespan of a civil dispute contracted from 145 days to just 28 days, generating a 41% reduction in procedural costs. The findings demonstrate that relying solely on party initiative is insufficient to cultivate a mediation culture. Establishing a robust national model requires statutory amendments that mandate pre-trial mediation attempts for specific civil categories, directly embedding restorative justice principles into the architectural core of the judicial system.